Engaging Secondary School Students in Learning Arabic Language through Flipped Classroom Using Creative MOOC Design - Abdel Rahman Ibrahim Suleiman Islieh; Zulkarnin Zakaria; Nurkhamimi Zainuddin; Nor Adlyizan Theis; Wan Ahmad Zakry Wan Kamaruddin; Mohd Zamrus Mohd Ali; Mohd Rushdan Mohd Jailani (JLLS, 2024)
Non-Indexed Publication